Diverticular colitis of the ascending colon preceding the onset of ulcerative colitis. (30th June 2014) - Maeshiro, Tatsuji; Hokama, Akira; Kinjo, Tetsu; Fujita, Jiro
Abstract : We present a case of diverticular colitis of the ascending colon preceding the onset of ulcerative colitis. A 58-year-old man presented with positive faecal occult blood test. Colonoscopy disclosed diverticular colitis of the ascending colon. After a year's follow-up, typical ulcerative colitis developed and diverticular colitis improved. Diverticular colitis is a newly established disorder of chronic segmental mucosal inflammation affected by diverticular disease. There is increasing recognition of such cases with diverticular colitis preceding ulcerative colitis. There may be a possible pathogenic relationship between the two diseases.